Species Density and Lead (Pb) Pollution in Mangrove Ecosystem, South Kalimantan - Anang Kadarsah; Dafiuddin Salim; Sadang Husain; Marta Dinata (Jurnal Biodjati, 2020)
Its crucial to get information about lead (Pb) heavy metal pollution from mining and oil palm plantation on species density in mangrove ecosystem, to anticipate its impacts. This study aimed is to compare the types and densities of vegetation in mangrove ecosystems allegedly due to mining in Setarap village, Tanah Bumbu Regency and oil palm plantations in Kuala Tambangan Village, Tanah Laut Regency. We also analysis the condition of waters (TDS, pH and DO) and organic content in sediments to acquire data from the South Kalimantan mangrove ecosystems. The results showed there were four species of true mangroves (Avicennia alba, Acanthus ebracteatus, Nypa fruticans and Rhizophora apiculate) could live well in the environment affected by mining or oil palm plantations. The species density for trees was low (933 ind/ha) for mangroves affected by coal mines, while those affected by oil palm plantations had higher densities (1,067 ind/ha). pH value of waters in affected area by coal mining showed more acidic value (pH 5.76) especially at the back, while those by palm oil plantations are more acidic (pH 6) in the estuary. Organic matter content in sediments affected by coal mines was in the range of 0.61-6.59%, while those affected by oil palm plantations showed higher values (0.12-2.19%). Lead heavy metal content (Pb) in waters affected by coal mines was 0.031-0.056 mg/L, while the area affected by oil palm plantations was of higher value (0.110-0.128 mg/L). Lead (Pb) levels in sediments indicate higher values than waters, which reach 3.512-6.046 mg/Kg (affected by coal mines), and in areas affected by oil palm plantations reaching 6.658-6.66 mg/Kg. The general conclusion is that vegetation densities in areas affected by coal mines are lower than oil palm plantations. The level of lead  (Pb) pollution in the sediments is higher than in the waters.